Social Contagion of Astrology in the Social Media amid COVID-19 Pandemic - Lopez, Kristoffer Romulo B.; Gaticales, Natalia P.; Provido, Alliyah Vanessa C.; Santelices, Samantha Mae B.; Arcinas, Myla M. (International Journal of Multidisciplinary: Applied Business and Education Research, 2021)
This cross-sectional study aimed to determine the associations of the extent of Social Contagion - Conscious Behavioral Response (CBR) towards Astrology on social media among Filipino Post-Millennial university students aged 18 to 23 years old with their demographics, Stress Level (SL), and Level of Susceptibility to Barnum effect (LSB) during the COVID-19 pandemic. A total of 406 respondents participated in the online survey and data were analyzed using descriptive and non-parametric inferential statistics. Findings showed that respondents have high SL, moderate CBR level, and high LSB. Female respondents were found to have significantly higher CBR Factor Scores compared too males (p< 0.000). Thus, the females tended to be more consumers of Astrology in the social media. Other variables tested (religion, p=0.128; residence type, p= 0.736; age, p= 0.339) showed no statistical significant difference between the sample’s CBR Factor Scores. Also, a person’s stress level during the COVID-19 pandemic (in terms of the situation’s manageability and uncertainty) revealed a statistical significant association with their susceptibility to the Barnum effect (odds ratio 1.252686, p= 0.002). Thus, the more stressed a person is, he tend to manifest higher consumption of Astrology related information in the social media due to high uncertainty and less capacity to control the situation despite high management capacity score. Furthermore, activities involved in the consumption of Astrology through social media revealed a positive moderate significant association with their level of susceptibility to the Barnum effect (r=0.603, p<0.000). In a pandemic situation, the females consumed more Astrology related information even if the information is vague and may be to general to absorbed. Overall, the higher the SL and the higher the CBR, the higher the LSB. Thus, in this period of COVID-19 pandemic, females are more susceptible to higher level of Barnum Effect as they consumed higher level of Astrology related information triggered by higher level of stress brought by the high level of uncertainty and low level of individual’s control to thee current pandemic situation